Hubungan Pola Asuh Orang Tua Dengan Perilaku Seksual Pada Remaja Di Sma Negeri 6 Halmahera Timur - kartika Kalo, Febi; Ernawati, Evy; Prabandasari, Febry Heldayasari (Universitas Prima Indonesia, 2024)
The increase in the number of girls getting married before they cross 19 is one of the clear signals of abnormal sexual behaviour among teenagers. Controlled behaviors, which surpass the usual developmental milestones of adolescence (most often influenced by family values), This study is aimed to reveal the relationship between parenting styles and sexual behavior in adolescents attending SMA Negeri 6 East Halmahera. Such a research is through the Spearmans Ranks statistical test analysis. The Spearman Ranks test is a possible method for analyzing the relationship of two variables on an ordinal scale at a level of significance α<0.05. Fieldwork was carried out between January–July 2024. This study used a sample of 60 students of SMAN 6 East Halmahera. Analysis was done using chi-square and data collection through questionnaire (p<0.05). Characteristics of respondents based on age frequency distribution found that the highest age was 16 years, namely 44 (73.3%) respondents. Frequency distribution of parenting style categories for teenage girls. The highest frequency was the authoritarian parenting category, with 32 (35.0%) respondents. The frequency distribution of sexual behavior among female adolescents was the highest, namely non-risky sexual behavior, 39 (68.4%) respondents. Statistical test results use Spearmans Ranks. The results of research calculations from the SPSS 23 output above show that the correlation between parenting patterns and sexual behavior is 0.378. From the statistical test results, it was found that the value p = 0.003 < ꭤ= 0.005. A notable correlation exists between parenting styles and the sexual behaviors exhibited by adolescents at SMA Negeri 6 East Halmahera)